Effectiveness of an Academic Motivation Training Model on Cognitive Flexibility, Academic Resilience, and Academic Motivation among Female Lower Secondary School Students in Tehran - Shokri Javan , Faezeh; Jahan, Faezeh; Rezaei, Noormohammad; Mehrafzoon , Dariush (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2026)
Objective: The present study aimed to examine the effectiveness of an academic motivation training model on cognitive flexibility, academic resilience, and academic motivation among female students in lower secondary schools in Tehran.Methods and Materials: This applied study employed a quasi-experimental design with a pretest–posttest format and a control group. The statistical population consisted of all female lower secondary school students in Tehran during the 2025–2026 academic year. Based on sample size estimation using G*Power software and Cohen’s criteria, 42 participants were selected through convenience sampling and randomly assigned to an experimental group (n = 21) and a control group (n = 21). The experimental group received training based on the academic motivation model over eight sessions, while the control group received no intervention. Research instruments included the Cognitive Flexibility Inventory developed by Dennis and Vander Wal (2010), the Academic Motivation Scale by Vallerand et al. (1992), and the Academic Resilience Scale by Cassidy (2016). Data were analyzed using analysis of covariance (ANCOVA) in SPSS at a significance level of 0.05.Findings: The results indicated that, after controlling for pretest effects, the academic motivation training model had a positive and statistically significant effect on cognitive flexibility, academic resilience, and academic motivation (p < 0.001). Specifically, significant differences were observed between the two groups in posttest scores for cognitive flexibility (F = 24.82, η² = 0.39), academic resilience (F = 32.27, η² = 0.46), and academic motivation (F = 43.80, η² = 0.53).Conclusion: Based on the findings, the academic motivation training model can be considered an effective educational intervention that enhances academic motivation, increases cognitive flexibility, and strengthens academic resilience among students. Therefore, implementing this model in educational settings and school counseling programs may improve learning quality, increase academic engagement, and facilitate better student adaptation to educational challenges.